Sosialisasi Ilmu Ekspor Kepada Mahasiswa Administrasi Bisnis Universitas Mulawarman - Lis Karlina; Bharata, Wira; Anwar, Khairil; Sanistasya, Poppy Alvianolita (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2025)
The large number of entrepreneurs or businesspeople in Indonesia who are not optimal in taking advantage of global market opportunities means that the value of exports in Indonesia is quite low when compared to other countries. the importance of conducting export outreach to partners, namely students as agents of change who will fightincrease the country's economic growth in the future. The aim of this socialization is to increase knowledge and skills as well as interest in being involved in international markets, especially in the export sector, for 30 Mulawarman University Business Administration students who of course have an interest in business. The implementation method used in the export-related material outreach program is through three stages. The first stage is preparation, thr second is implementation, and the third is evaluation. Evaluation was carried out using a Google Form given to participants. Based on the evaluation at the end of the socialization activity, it can be concluded that the student participants were satisfied with the export-related material that had been delivered. It can be concluded that this socialization program is running as it should and as planned.